TLR9 in MAFLD and NASH: At the Intersection of Inflammation and Metabolism - Shepard, Christopher R. (Frontiers in Endocrinology, 2021)
Toll-Like Receptor 9 (TLR9) is an ancient receptor integral to the primordial functions of inflammation and metabolism. TLR9 functions to regulate homeostasis in a healthy system under acute stress. The literature supports that overactivation of TLR9 under the chronic stress of obesity is a critical driver of the pathogenesis of NASH and NASH-associated fibrosis. Research has focused on the core contributions of the parenchymal and non-parenchymal cells in the liver, adipose, and gut compartments. TLR9 is activated by endogenous circulating mitochondrial DNA (mtDNA). Chronically elevated circulating levels of mtDNA, caused by the stress of overnutrition, are observed in obesity, metabolic dysfunction-associated fatty liver disease (MAFLD), and NASH. Clinical evidence is supportive of TLR9 overactivation as a driver of disease. The role of TLR9 in metabolism and energy regulation may have an underappreciated contribution in the pathogenesis of NASH. Antagonism of TLR9 in NASH and NASH-associated fibrosis could be an effective therapeutic strategy to target both the inflammatory and metabolic components of such a complex disease.